The Frequency, Severity, and Risk Factors of Hickman CatheterRelated Complications in Pediatric Cancer Patients: A Single-Center Experience from Bosnia and Herzegovina - Zlatan Zvizdic; Emin Zaimovic; Emir Milisic; Asmir Jonuzi; Una Glamoclija; Semir Vranic (AVES Yayincilik, 2024)
Objective: This study aimed to identify the frequency, severity, and risk factors associated with Hickman catheter-related complications in children with hemato-oncological malignancies at the largest pediatric tertiary care unit in Bosnia and Herzegovina. Materials and Methods: A cross-sectional study was conducted on a cohort of pediatric cancer patients who underwent Hickman central venous catheters (CVCs) between January 2019 and December 2022. Mechanical, infectious, and thrombotic Hickman catheter-related complications were evaluated and analyzed. We also investigated possible risk factors associated with these complications. Results: Seventy-one Hickman CVCs were inserted in 68 children (44 boys and 24 girls) at a mean age of 6.9 ± 4.6. Forty (58.8%) children had hematological malignancies and 28 (41.2%) solid cancers. The median follow-up after Hickman CVC insertion was 190 days (95% CI [160-212]) for 12 644 catheter days. During follow-up, 10 (14.1%) mechanical, 7 (9.9%) infectious, and 1 (1.4%) thrombotic complications were recorded (0.8, 0.48, and 0.08 for mechanical, infectious, and thrombotic complications per 1000 catheter days, respectively). A slightly higher incidence of complications was recorded in children with hematological malignancies (1.59 per 1000 catheter days) compared with children with solid cancers (1.22 complications per 1000 catheter days). Conclusion: Using Hickman CVCs for long-term venous access in infusional chemotherapy for pediatric cancer patients is safe but is associated with significant morbidity.